Single-Layered Phase-Change Metasurfaces Achieving Polarization- and Crystallinity-Dependent Wavefront Manipulation - Jie Hu; Yujie Chen; Wenting Zhang; Ziyi Tang; Xiang Lan; Qinrong Deng; Hengyu Cui; Ling Li; Yijia Huang (Photonics, 2023)
As a promising platform for versatile electromagnetic (EM) manipulations, metasurfaces have drawn wide interest in recent years due to their unique EM properties and small footprints. However, although great efforts have been made to achieve multifunctionalities, the design of tunable metasurfaces with high compactness is still challenging. Here, a simple yet powerful design methodology for single-layered reconfigurable metasurfaces composed of nonvolatile phase-change material Ge2Sb2Se4Te1 (GSST) is proposed with average working amplitudes of 72.6% and 53% at different crystallization levels. The proposed metasurfaces could not only enable independent phase control at different crystallization levels but also introduced another polarization degree of freedom. As a proof of concept, we numerically demonstrate three kinds of metadevices in the infrared region achieving a multi-focus metalens with tunable foci, multistate vortex beam generator with adjustable topological charges and multi-channel meta-hologram with three independent information channels. It is believed that these multifunctional metasurfaces with both tunability and compactness are promising for various applications including information encryption, chiroptical spectroscopy, chiral imaging and wireless communication.